2016
DOI: 10.1002/slct.201600803
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty Principle in the Elucidation of the Extraction Mechanism of Ions from Aqueous towards Ionic Liquid Phases. PtCl62− and [C1C8IM][NTf2] as a Textbook Case

Abstract: The extraction mechanism of Pt(IV) from aqueous HCl solutions towards the ionic liquid 1-octyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide ([C 1 C 8 IM][NTf 2 ]) is deciphered. To that end, aqueous speciation of Pt(IV) as a function of HCl was studied by 195 Pt NMR. Influence of the concentration of HCl (ranging from 1 to 12 M) and of the initial concentration of Pt (IV) (ranging from 10 À5 to 10 À2 M) in the aqueous phase on the distribution coefficients of Pt(IV) was systematically investigated. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 38 publications
1
21
1
Order By: Relevance
“…Based on the large D values for large [RhCl 4 ] − amounts, the proposed mechanism cannot cope without involving [RhCl 4 ] − . Rh extraction can be either described by an ion exchange model or by an ion pair formation process [14]. The ion exchange model can be written as:RhCl4+trueCl¯trueRhCl4¯+Cl where species capped with a bar correspond to species in the IL phase.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the large D values for large [RhCl 4 ] − amounts, the proposed mechanism cannot cope without involving [RhCl 4 ] − . Rh extraction can be either described by an ion exchange model or by an ion pair formation process [14]. The ion exchange model can be written as:RhCl4+trueCl¯trueRhCl4¯+Cl where species capped with a bar correspond to species in the IL phase.…”
Section: Resultsmentioning
confidence: 99%
“…ILs have low viscosity. An in-depth study of the Pt extraction mechanism was reported by Papaiconomou et al in 2016 [56]. They investigated the extraction mechanism of Pt using hydrophobic imidazolium-based ILs (e.g., C 8 mimTf 2 N).…”
Section: Imidazolium-based Ilsmentioning
confidence: 99%
“…They found that the mechanism of metal extraction is typically mainly based on either ion exchange or ionpair formation, with the latter being more favorable because it avoids undesirable loss of the ILs in the aqueous phase [55]. They also found that both the ion exchange and ion-pair formation mechanisms are equally applicable to metal extraction [56]. This uncertainty principle can also be applied to extraction of charged metal complexes with any hydrophobic IL.…”
Section: Imidazolium-based Ilsmentioning
confidence: 99%
“…Furthermore, understanding the corrosion of noble metals has started to emerge as an important issue from the perspective of environmentally friendly recycling strategies, 16 where organic solvents show much promise. [17][18][19][20] ICP-MS analysis of organic matrices is not as common as in case of aqueous matrices and presents a much greater challenge in tackling instrumental settings and several unusual spectral interferences. 21 The presence of high levels of organic solvents increases the vapor pressure of the sample solution, which is circumvented by cooling the ICP-MS spray chamber to −5°C.…”
Section: Introductionmentioning
confidence: 99%